Translating evidence into practice in acute respiratory distress syndrome: teamwork, clinical decision support, and behavioral economic interventions. Issue 5 (October 2017) - Sjoding, Michael W.
Abstract : Purpose of review: Although the treatment of the acute respiratory distress syndrome (ARDS) with low tidal volume (LTV) mechanical ventilation improves mortality, it is not consistently administered in clinical practice. This review examines strategies to improve LTV and other evidence-based therapies for patients with ARDS. Recent findings: Despite the well established role of LTV in the treatment of ARDS, a recent multinational study suggests it is under-utilized in clinical practice. Strategies to improve LTV include audit and feedback, provider education, protocol development, interventions to improve ICU teamwork, computer decision support, and behavioral economic interventions such as making LTV the default-ventilator setting. These strategies typically target all patients receiving invasive mechanical ventilation, effectively avoiding the problem of poor ARDS recognition in clinical practice. To more effectively administer advanced ARDS therapies, such as prone positioning, better approaches for ARDS recognition will also be required. Summary: Multiple strategies can be utilized to improve adherence to LTV ventilation in ARDS patients.